Integration of statistical process control and engineering process control in reactor system / Nur Izzati Simaa Abdul Khar - Abdul Khar, Nur Izzati Simaa (2017)
The purpose of this study is to investigate the integration of Statistical ProcessControl and Engineering Process Control in batch reactor system. The Shewhart control chart, Cumulative Sum(CUSUM) and Exponential Moving Average (EMWA) control chart have been aproached to evaluate the best and effective control to monitor thebatchreactor.Integration of Statistical Process Control (SPC) and EngineeringProcessControl(EPC) in the system for the purposed to monitoring and adjusting the disturbanceand fault that cause variation of system. This technique can help to improve processproductivity and product quality. Batch reactor have a bigger issue in controllingthetemperature and also lack of on-line monitoring and controlling worst the problem. Thebatch esterification reactor system used as case study. The feedback PIDcontroller wasinstalled in the reactor system to make the adjustment of the process response toavoidthe process drift away from the target value which is 310K. The data of the process that simulate from MATLAB was extracted, and calculated to be monitor. This monitoringprocess using different type of control chart; Shewhart, Cumulative SumandExponential Moving Average control chart by using Minitab software. The experimental result, proved that CUSUM and EMWA chart is more effective than Shewhart becausecan quickly detecting mean shift that are small relative to measurement system.